The integrated circus : the New Right and the restructuring of global markets - Marchak, M. Patricia (McGill-Queen's University Press, 1991)
Focusing on the conservative ideologies and political organization of the New Right, this study explores its impact on the development of a global marketplace after World War II. It examines the changes such political strategies created in the world economy, and the effect on individual countries.